Some Identifiable Factors Responsible for the Variation in Cocoa Production in Nigeria and Other Cocoa Producing Nations, Adjudicated by Their Contributions to the Global Market - Etaware, Peter Mudiaga (Frontiers in Agronomy, 2022)
The increasing human population is indeed responsible for the upsurge in the demand for cocoa products and the saddling pressure on the global cocoa market. Sadly, the contributions of some major producers like Nigeria, Brazil, Ghana etc., to the global cocoa market is dwindling (while others are appreciating). Climate change, diseases and poor farm management have been identified as major factors affecting global cocoa production. Nigeria, was the major focus of this research. Cocoa farms were investigated (Nigeria only), black pod disease (BPD) pressure was described by ETAPOD (a model for black pod disease prediction), while climate and cocoa production data were obtained from the relevant databases. On the global scene, Ghana, Nigeria, Cameroon, Brazil, Ecuador and Colombia experienced shortfall in their contribution to global cocoa production from 26.15, 20.55, 7.45, 12.14, 4.07 and 1.40%, respectively (1970s), to 16.99, 6.31, 5.67, 4.54, 3.96 and 1.09%, respectively (2000s). Cross River State, Nigeria’s leading producer of cocoa (1970-1990s) is currently ranked 3rd in the nation. Unfortunately, cocoa farmers in Nigeria are completely dependent on pesticide application (100%) to save their crops. A prognosis of global BPD outbreak showed that Honduras (15.1%) and Lagos, Nigeria (14.4%) are foremost hotspots for BPD invasion. Hopefully, scientific advancement in cocoa production might be the key to these problems.